2021
DOI: 10.1007/s10340-020-01317-4
|View full text |Cite
|
Sign up to set email alerts
|

Organic anion-transporting polypeptides are involved in the elimination of insecticides from the red flour beetle, Tribolium castaneum

Abstract: Organic anion-transporting polypeptides (OATPs) are integral membrane transporters that mediate cellular uptake of a broad range of substrates in humans. The functions of OATPs in insects are less well investigated and only poorly understood. A large number of compounds potentially toxic to insects are organic anions that include secondary plant and insecticide-derived metabolites. Some insect OATP genes are expressed in metabolic, neuroprotective and excreting tissues, and they are co-expressed together with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 33 publications
3
9
0
Order By: Relevance
“…This is in line with DmOatp74D, which seems to be essential for the development of larval stages since homozygous mutant flies arrested at L1 stage, failing to molt to the second larval instar [24]. Our results are also consistent with a previous study in Tribolium castaneum, in which decreased larval survival and failure of pupation was observed upon silencing of TcOATP4-C1, a putative ortholog of the Drosophila Oatp74D [55]. Increased larval mortality was also observed in Aedes aegypti upon silencing of EcI-2 which induced 70-80% lethality [26].…”
Section: Oatp74d Is Essential For Lepidopteran Insect Development And...supporting
confidence: 92%
“…This is in line with DmOatp74D, which seems to be essential for the development of larval stages since homozygous mutant flies arrested at L1 stage, failing to molt to the second larval instar [24]. Our results are also consistent with a previous study in Tribolium castaneum, in which decreased larval survival and failure of pupation was observed upon silencing of TcOATP4-C1, a putative ortholog of the Drosophila Oatp74D [55]. Increased larval mortality was also observed in Aedes aegypti upon silencing of EcI-2 which induced 70-80% lethality [26].…”
Section: Oatp74d Is Essential For Lepidopteran Insect Development And...supporting
confidence: 92%
“…Recent studies in Drosophila have shown that ecdysone, the primary steroid hormone in insects, requires a membrane transporter EcI to enter its target cells and exert its genomic effects through EcR (6, 25). Although this critical function of EcI in ecdysone signaling seems to be highly conserved among other insect species (7), we noticed that EcI orthologs are unexpectedly missing in mosquitoes. In the present study, we characterized additional ecdysone importers, EcI-2, 3, and 4, in both Drosophila and Aedes .…”
Section: Discussionmentioning
confidence: 74%
“…Although it has long been assumed that ecdysone can pass through the cell membrane through simple diffusion, we recently demonstrated that an organic anion-transporting polypeptide (OATP), which we named Ecdysone Importer (EcI), is required for cellular uptake of ecdysone in the fruit fly Drosophila melanogaster (6). EcI orthologs are found among a wide variety of insects (6), and it is likely that its critical function as a mediator of ecdysone signaling is highly conserved in other insect species (7).…”
Section: Introductionmentioning
confidence: 99%
“…Because TcABCC‐5V was particularly strongly upregulated in the fat body, it was suggested that this transporter has a function in the export of DFB metabolites (possibly conjugated with glutathione) generated in fat body cells (Rösner & Merzendorfer, 2020). Interestingly, the import of DFB into fat body cells appears to be mediated by the organic anion transporter TcOATP5‐A1.1 , because the expression is strongly upregulated in response to DFB in the fat body and RNAi‐mediated gene silencing of TcOATP5‐A1.1 results in increased susceptibility to the insecticide (Rösner et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%